Nanostructured Films and Coatings 2000
DOI: 10.1007/978-94-011-4052-2_7
|View full text |Cite
|
Sign up to set email alerts
|

Electroless Deposited Nanostructured NiCo Films

Abstract: Nanostructured metal films and coatings with unique properties can be synthesized using solution chemistry. In this paper, the non-aqueous electroless polyol synthesis, characterization and properties of NiCo films are discussed. IntroductionNanostructured films and coatings with unique properties can be fabricated by many methods. Physical vapor techniques, such as thermal evaporation and sputtering, are generally line-of-sight processes suited for deposition on planar surfaces. The limitation in these proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…On the other hand, it has been demonstrated that nanoporous materials with tailored functionality can be developed using aerogels as a flexible and robust material platform [10][11][12][13][14][15][16]. Furthermore, metal loading of aerogels should allow one to fine-tune material properties by exploiting the size-effect frequently observed for metal nanoparticles [17] and other nanostructured materials [18]. The techniques which have been developed to synthesize metal-loaded aerogels can be divided into two groups based on whether the metal is added before or after the sol-gel process.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been demonstrated that nanoporous materials with tailored functionality can be developed using aerogels as a flexible and robust material platform [10][11][12][13][14][15][16]. Furthermore, metal loading of aerogels should allow one to fine-tune material properties by exploiting the size-effect frequently observed for metal nanoparticles [17] and other nanostructured materials [18]. The techniques which have been developed to synthesize metal-loaded aerogels can be divided into two groups based on whether the metal is added before or after the sol-gel process.…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructured films and coatings exhibit outstanding physical properties widely exploited in contemporary high technologies (see [1][2][3][4][5][6]). In particular, semiconductor nano-islands (quantum dots) and nano-wires are the subject of intensive theoretical and experimental studies owing to their great technological potential for device applications (see ).…”
Section: Introductionmentioning
confidence: 99%